Hypertension continuum of care: Blood pressure screening, diagnosis, treatment, and control in a population‐based cohort in Haiti. Issue 3 (24th February 2022) - Metz, Miranda; Pierre, Jean Lookens; Yan, Lily Du; Rouzier, Vanessa; St‐Preux, Stephano; Exantus, Serfine; Preval, Fabyola; Roberts, Nicholas; Tymejczyk, Olga; Malebranche, Rodolphe; Deschamps, Marie Marcelle; Pape, Jean W.; et al.
Abstract: Cardiovascular disease (CVD) is the number one cause of death in low‐income countries including Haiti, with hypertension (HTN) being the leading risk factor. This study aims to identify gaps in the HTN continuum of screening, diagnosis, treatment, and blood pressure (BP) control. Sociodemographic and clinical data were collected from a population‐based sample of adults ≥18 years in Port‐au‐Prince (PAP) from March 2019 to April 2021. HTN was defined as systolic BP ≥ 140 mmHg, diastolic BP ≥ 90 mmHg, or use of antihypertensive medication. Screening was defined as ever having had a BP measurement; diagnosis as previously being informed of a HTN diagnosis; treatment as having taken antihypertensives in the past 2 weeks; and controlled as taking antihypertensives and having BP < 140/90 mmHg. Factors associated with attaining each step in the continuum were assessed using Poisson multivariable regressions. Among 2737 participants, 810 (29% age‐standardized) had HTN, of whom 97% had been screened, 72% diagnosed, 45% treated, and 13% controlled. There were no significant differences across age groups or sex. Obesity (BMI ≥ 30) was a significant factor associated with receiving treatment compared to normal weight (BMI < 25), with a prevalence ratio (PR) of 1.5 (95% CI 1.1–2.0). Having secondary or higher education was associated with higher likelihood of controlled BP (PR 1.9 [95% CI 1.1–3.3]). In this urban Haitian population, the greatest gaps in HTN care are treatment and control. Targeted interventions are needed to improve these steps, including broader access to affordable treatment, timely distribution of medications, and patient adherence to HTN medication.